2021
DOI: 10.1111/jace.18147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humidity on friction, wear, and plastic deformation during nanoscratch of soda lime silica glass

Abstract: Physical flaws and defects on glass surfaces are known to reduce the mechanical strength and chemical durability of glass. The formation of surface defects depends not only on the mechanical conditions of the physical contact but also on the environment in which the contact is made. In this study, the nanoscratch behavior of soda lime silica (SLS) glass was investigated in 10% and 60% relative humidity (RH) conditions. Based on the evolution of friction and scratch depth, the deformation of SLS glass surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Moreover, previous work has demonstrated that failure mechanisms during indentation testing under normal stress made with a sharp indenter are markedly different from the damage mode under interfacial shear (friction) generated by a smooth counter‐surface 62 . For example, the compressive stress that increases hardness in chemically strengthened glasses has been shown to deteriorate the high RH wear resistance when evaluated under frictional shear 14,63 . This is because wear tests involve mechanochemical reactions, including hydrolysis reactions that are enhanced by the distortion of the silicate network 16,25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous work has demonstrated that failure mechanisms during indentation testing under normal stress made with a sharp indenter are markedly different from the damage mode under interfacial shear (friction) generated by a smooth counter‐surface 62 . For example, the compressive stress that increases hardness in chemically strengthened glasses has been shown to deteriorate the high RH wear resistance when evaluated under frictional shear 14,63 . This is because wear tests involve mechanochemical reactions, including hydrolysis reactions that are enhanced by the distortion of the silicate network 16,25 …”
Section: Resultsmentioning
confidence: 99%
“…62 For example, the compressive stress that increases hardness in chemically strengthened glasses has been shown to deteriorate the high RH wear resistance when evaluated under frictional shear. 14,63 This is because wear tests involve mechanochemical reactions, including hydrolysis reactions that are enhanced by the distortion of the silicate network. 16,25 The high wear rate for the NAS glass (R = 0) can be intuitively explained by the hygroscopic nature of the glass, discussed previously, and shown graphically in Figure S2.…”
Section: Mme On Mechanochemical Propertiesmentioning
confidence: 99%
“…It should also be noted that environmental effects, such as humidity, can alter the interfacial friction between the indenter surface and the glass surface moving due to shear flow, which eventually alter the degree of plastic deformation. 126…”
Section: Relationship Between Expected Modulus Of Rupture ("Mor") And...mentioning
confidence: 99%
“…A more fundamental approach would be to couple tribological tests with structural investigation tools revealing how the residual stresses interact with a statistical distribution of flaws. It should also be noted that environmental effects, such as humidity, can alter the interfacial friction between the indenter surface and the glass surface moving due to shear flow, which eventually alter the degree of plastic deformation 126 …”
Section: What Is Yet To Be Learned About Indentation and Abrasion In ...mentioning
confidence: 99%
“…Plastic deformation wear, as characterized by flow and yielding, contributes to material displacement and surface modification. Grooving, surface flattening, flow patterns and micro cracking are the microstructural features of Plastic deformation wear [4]. Delamination wear occurred by the peeling of the surface categorized by surface flaking, material fracture, crack networks and void formation [5].…”
Section: Introductionmentioning
confidence: 99%